Essential Factors in Predicting the Need for Angio-Embolization in the Acute Treatment of Pelvic Fracture with Hemorrhage - Seok-Won Yang; Hee-Gon Park; Sung-Hyun Kim; Sung-Hyun Yoon; Seung-Gwan Park (Journal of Trauma and Injury)
Purpose The purpose of this study was to determine the essential factors for prompt arrangement of angio-embolization in patients with pelvic ring fractures. Methods A total of 62 patients with pelvic ring fractures who underwent angio-embolization in Dankook University Hospital from March 2013 to June 2018 were retrospectively reviewed. There were 38 men and 24 women with a mean age of 59.8 years. The types of pelvic ring fractures were categorized according to the Tile classification. Patient variables included sex, initial hemoglobin concentration, initial systolic blood pressure, transfused packed red blood cells within 24 hours, Injury Severity Score (ISS), mortality rate, length of hospital stay, and time to angio-embolization. Results The most common pelvic fracture pattern was Tile type B (n=34, 54.8%). The mean ISS was 27.3±10.9 with 50% having an ISS ≥25. The mean time to angio-embolization from arrival was 173.6±89 minutes. Type B (180.1±72.3 minutes) and type C fractures (174.7±91.3 minutes) required more time to angio-embolization than type A fractures (156.6±123 minutes). True arterial bleeding was identified in types A (35.7%), B (64.7%), and C (71.4%). Conclusions It is important to save time to reach the angio-embolization room in treating patients with pelvic bone fractures. Trauma surgeons need to consider prompt arrangement of angio-embolization when encountering Tile type B or C pelvic fractures due to the high risk of true arterial bleeding.